Mente e cérebro, ciências cognitivas e ciências sociais - Rodolfo Eduardo Scachetti (Ciências Sociais Unisinos)
This paper discusses the traditional philosophical debate concerning body and spirit that has formed a multidisciplinary field of researches about brain and mind in the twentieth century, called cognitive sciences. Among the various divergent positions in this area, three of them had their nuances about the future of this exploited enterprise, and also their relations with the social sciences that basically move in these directions, (i) the defence of the singularity of human sciences' object considered in the philosophical consciousness model as intentionality, (ii) the searching of a biological understanding of the mind, also viewed in this case as intentionality and consciousness, and finally, (iii) the critic of the notions of intentionality and consciousness through the cybernetic and also the cognitive sciences achievements, that can feed a new relation between humans and machines.